Kualitas Arang Aktif Kayu Gelam dan Aplikasinya untuk Meningkatkan Kualitas Air (Activated Charcoal Quality of Gelam Wood and Its Application to Improve Water Quality) - Alpian, Alpian; Prayitno, TA; Sutapa, JP Gentur; Budiadi, Budiadi (Jurnal Ilmu dan Teknologi Kayu Tropis, 2010)
Gelam (Melaleuca cajuputi) is the dominant tree species grown in swamp forests, especially in tidal areas in Central Kalimantan. Gelam wood has been used for construction and biomass energy, which is due to high density of wood. Previously studies reported that the quality of charcoal from wood stems of Gelam was better than that from roots, fruits, flowers, branches and leaves. The study was to investigate the characteristics of activated charcoal from wood stem of gelam which taken from different site and growth stages of the tree, and its utilizations for water quality improvement. The parameters observed were yield, moisture content, volatile matter content, ash content, fixed carbon, absorption of benzene, iodine and methylene blue. The Gelam wood from different growth site and stage of trees (saplings, poles, trees) can be used as raw material for activated charcoal production. The quality of activated charcoal fulfilled the quality requirements of technical activated charcoal (SNI 06-3730-1995), activated charcoal for the purification of edible oil (SNI 06-4262-1996) and drinking water (SNI 06-4253-1996), except for absorption of benzene. Generally, the quality of water treated by activated charcoal increased and fulfilled the requirements of clean water standards (Departemen Kesehatan 1990).